Economic growth through the lenses of education, entrepreneurship, and innovation - Simona Andreea Apostu; Lindita Mukli; Mirela Panait; Iza Gigauri; Eglantina Hysa (Administrative Sciences, 2022)
Economic growth is a major goal pursued by public authorities but can be achieved with the involvement of several categories of stakeholders given the complexity of the phenomenon and the many influencing factors. In this research paper, the authors analyze specific current issues that are representative as influencers of economic growth. This study brings into focus the importance of education, particularly tertiary education, entrepreneurship skills, and innovation capacities of businesses. The objectives are (1) to find out if tertiary education leads to economic growth; (2) to examine if innovation is one of the promotors of economic growth; and (3) to discuss the impact of the dynamic of businesses (enterprise birth) on economic growth. The methodology used in this research is panel regression (static model) for a sample consisting of 30 European countries for the period 2003-2020. The main findings are associated with a positive influence of tertiary education on economic growth, whereas the two other variables, that of entrepreneurship and innovation, are found to be insignificant for this time period.
Keywords: 350; economic growth; education; entrepreneurship; innovation